Combination of inclusive and differential t-t charge asymmetry measurements using ATLAS and CMS data at √s = 7 and 8 TeV - Alconada Verzini, María Josefina (2018)
This paper presents combinations of inclusive and differential measurements of the charge asymmetry (AC) in top quark pair (t-t) events with a lepton+jets signature by the ATLAS and CMS Collaborations, using data from LHC proton-proton collisions at centre-of- mass energies of 7 and 8 TeV. The data correspond to integrated luminosities of about 5 and 20 fb-1 for each experiment, respectively. The resulting combined LHC measurements of the inclusive charge asymmetry are ALHC7C = 0.005±0.007 (stat) ±0.006 (syst) at 7TeV and ALHC8C= 0.0055 ± 0:0023 (stat) ± 0.0025 (syst) at 8 TeV. These values, as well as the combination of AC measurements as a function of the invariant mass of the t-t system at 8 TeV, are consistent with the respective standard model predictions.